Text in French written on the back. Left, with hat, Mac (Delmarle), in the centre: Jeanne en Eugène Humbert, right: Paul Philippe ? - Fleury, F, (1913)
Text in French written on the back. Left, with hat, Mac (Delmarle), in the centre: Jeanne en Eugène Humbert, right: Paul Philippe ?.